Thermodynamic approach for hydrogen production from the steam reforming reaction of aromatic hydrocarbons (BTX) - Kim, Min Ju; Gong, Ji Hyeon; Jeon, Kyung Won; Shim, Jae Oh; Jang, Won Jun (International Journal of Hydrogen Energy, 2024)
This study investigates the preferred reaction conditions through thermodynamic analysis to produce hydrogen from the steam reforming of BTX, a mixture of benzene (C6H6), toluene (C7H8), and xylene (C8H10). A thermodynamic equilibrium analysis employing the minimization of Gibbs free energy was used to investigate the effects of temperatures (200–1000 °C), S/C ratios (0.5–4.0), and pressure (1–20 atm) on the molar fraction at equilibrium, conversion (C6H6, C7H8, C8H10), selectivity (C, CO, CO2, CH4), moles (H2 and CH4), and H2 yield. The steam reforming of BTX is a complex process that involves various reactions such as steam reforming, cracking, carbon formation, and water-gas shift reactions. It was confirmed that cracking does not occur above 700 °C, and carbon deposition does not form with S/C ratio higher than 3.0. In addition, the steam reforming reaction of BTX was found to be favorable at low pressure. To minimize undesirable reactions, such as cracking and carbon deposition, and enhance hydrogen production, the optimal conditions were identified as S/C ratio of 3.0, temperature of at least 700 °C, and atmospheric pressure. This research contributes valuable insights into the steam reforming of BTX, highlighting the optimal conditions that maximize hydrogen production while minimizing unwanted reactions. By identifying these conditions, the study underlines the importance and innovation in the hydrogen production field, potentially guiding future research and industrial applications.
Keywords: BTX; Carbon deposition; CH 4; Effects of temperature; Minimisation; Optimal conditions; Reaction conditions; Thermo dynamic analysis; Thermodynamic approaches; Thermodynamics equilibrium analysis; BTX; Carbon deposition; Hydrogen; Steam reforming; Thermodynamic analysis